Tracing the Feminization of Internal Migration in Nepal Through Census Data - Shrestha, Bidhya; Khatiwada, Padma Prasad; Gurung, Yogendra B. (Geographical Journal of Nepal, 2026)
The gender dimension of migration not only indicates a growing number of female migrants but also demands for a gender-sensitive analysis. While the trend has been increasingly identified by international migration studies, internal female migration in Nepal remains under researched. This study has traced gender aspect of internal migration by analysing trends in sex ratios of five consecutive national censuses—1981, 1991, 2001, 2011, and 2021—disaggregated by ecological zones (Mountain, Hill, and Tarai). This is termed as feminization of migration in this paper. The finding shows a consistent declining trend in sex ratio, especially in the Mountain and Hill zones, suggesting a rise in female migration. Using sex ratio as a proxy, this study explores process and perspective both in terms of sex ratio trend and reasons of migration. Drawing on Mahler and Pessar’s gendered geographies of power framework, this study highlights how structural forces, such as labor demands, education and shifting norms, interact with women’s agencies in shaping migration trajectories. The finding emphasized the necessity of gender-sensitive migration policy that identify women’s diverse motivations and vulnerabilities in Nepal’s shifting demographics.